Pengaruh Content Marketing dan Electronic.Word.of.Mouth.(e-WOM) Terhada.p Keputusan Penggunaan Pada.Aplikasi Tiktok - Sukainah, Ishma Arij; Sarah, siti (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Technological advances are advancing rapidly today, particularly in areas such as communication, marketing, and consumer behavior. These advancements have significanly transformed how individuals communicate, obtain information and decide on buying or using products.One key shift is the rising prevalence of online social networks and digital platforms such as Tiktok. Tiktok has evolved beyond being a mere entertainment platform into a powerful marketing and communications tool. This research focuses on the noticeable increase in electronic word of mouth and content marketing on Tiktok. These are believed to influence consumers' decisions to use the app, especially among active users. The primary aim of this research is to explore how far content marketing, e-WOM powering users' decisions to use the Tiktok app. The quantitative research method employed utilized a survey approach in which questionnaires were distributed to 100 respondents via Google Forms. The gathered information was subsequently examined through various forms of linear regression analysis. The findings indicate that electronic word of mouth (e-WOM) and content marketing significantly and beneficially affect users' decisions to use the platform